New guidelines for the management of patients with Behcet's disease/syndrome (EULAR, 2018) - T. A. Lisitsyna; Z. S. Alekberova; R. G. Goloeva (Научно-практическая ревматология)
The article is devoted to the new guidelines of EULAR on the management of patients with Behcet's disease/syndrome (BD), which include 5 principles and 10 specific recommendations for the treatment of various organ lesions. The methodology of their creation, as well as unresolved issues of management of patients with BD, which are planned to be investigated in the future, are considered.